Eucharystia w statutach potrydenckich synodów włocławskich i innych aktach prawno-duszpasterskich biskupa Stanisława Karnkowskiego - Gręźlikowski, Janusz (Prawo Kanoniczne, 2005)
Important and significant person in the church reform and reception the Trident reform in diocese of Włocławek is person of the bishop Stanisław Karnkowski (1567-1581), next arcbishop gnieźnieński and primate of Poland (1582-1603). Through his two synods of the dioceses of Włocławek of 1568 and 1579 and another acts law-priesthood introduce the reform of Trent and increase change the face of the Włocławek Church. Karnkowski realize, that renovation of priesthood and reparation religious life must to have beginning in reform of the clergy, to keep church discipline and instruction control sacramental life. About this he take care in legislation and pastoral activity. Among the rich problems of the two Włocławek synods and another law-priesthood acts, such as The collection of the synods constitutions of 1579 and Admonitiones, many places Karnkowski as bishop of Włocławek dedicated of performance and receive of the sacraments in this principally the Eucharistic. Through his law-priesthood activity Karnkowski to wish order whole question related with Eucharistic sacrament, his performing, receiving, keeping and cult. This activity was systematic wide and totality. Its refer to the activity exclusively law, intend to do universal of Eucharistic. This activity had practical character, because to serve renovation priesthood in spirit of the Trident Council and increase to know through the clergy problems connected with morality theology, sacramentaly and liturgy. Noteworthy is wide base synod resolution and another law-priesthood acts on the decree of Trident Council as for testify about great care of the bishop Karnkowski abut introduce Trident reform in diocese Włocławek life. Analysis the above acts of law and another activity authorize to find that Karnkowski to wish that perform and receive this sacrament to be celebrated in harmony with Trident norms, thus through his activity to increase to rebirth religious and sacrament life.